Quantitation of human peptides and proteins via MS: review of analytically validated assays. (July 2014) - Chappell, Derek L; Lassman, Michael E; McAvoy, Thomas; Lin, Mingxiang; Spellman, Daniel S; Laterza, Omar F
Since the development of monoclonal antibodies in the 1970s, antibody-based assays have been used for the quantitation of proteins and peptides and, today, they are the most widely used technology in routine laboratory medicine and bioanalysis. However, in the last couple of decades, liquid chromatography-mass spectrometry/mass spectrometry (LC–MS/MS) techniques have been adopted in the quantitation of small molecules, and more recently have made significant contributions in the quantitation of proteins and peptides. In this article, we will review clinical MS-based assays for endogenous peptides, proteins, and therapeutic antibodies, for which validated methods exist. We will also cover the measurement of protein turnover and the unique solutions that MS can offer in this field.